EBV-positive mucocutaneous ulcer arising in a post-hematopoietic cell transplant patient: A difficult diagnosis - Mariateresa Giaimo; Lucia Prezioso; Benedetta Cambò; Benedetta Dalla Palma; Federica Falcioni; Amelia Rinalidi; Alessandro Tafuni; Gianluca Di Rienzo; Valerio Copelli; Pellegrino Crafa; Daniele Vallisa (Archives of Clinical Gastroenterology - Peertechz Publications, 2021)
Background: EBV-positive Mucocutaneous Ulcer (EBV-MCU) is a newly recognized clinicopathological entity characterized by ulcerated lesions affecting cutaneous and/or mucosal sites typically in immunosuppressed patients. To our knowledge, only 2 cases of EBV-MCU have been described following allogeneic Hematopoietic stem cell transplantation (alloHSCT). Here we describe a case of EBV-MCU that developed acutely 22 days after HSCT with massive intestinal bleeding and rapidly worsening clinical condition. Case report: A 46-year-old male was diagnosed with Severe Aplastic Anemia (SAA) and underwent immunosuppressive therapy. Because lacking response, he subsequently underwent Matched Unrelated Donor (MUD) allogeneic HSCT after Myeloablative Conditioning (MAC). The donor and the patient were IgG positive and IgM negative for EBV Viral Capsid Antigen (VCA) before transplantation, while the donor was seronegative for CMV and the patient was seropositive. Hematologic recovery was reached rapidly after engraftment. During aplasia, the patient experienced Hepatic Veno-occlusive Disease, treated with Defibrotide. From day 22 after allografting, the patient developed worsening melena and rectal bleeding. CT angiography of the abdomen showed multiple jejunal bleeding sites, compatible with severe erosion of the intestinal mucosa. EGDS, Colonoscopy, and Capsule Endoscopy confirmed multiple duodenal and jejunal ulcers. Duodenal biopsies were performed for histological evaluation. PCR for EBV-DNA and CMV-DNA was negative throughout the course. Stool cultures were negative for viral, bacterial, and fungal infections. The patient was empirically treated with steroids and Ganciclovir, associated with massive transfusional support. After many attempts to stop the bleeding with multiple intestinal peripheric arterial embolization and medical therapy, because of worsening clinical conditions, the patient was indicated to laparotomy with a double ileostomy to remove the bleeding intestinal tract. Just before the surgical intervention, histological findings confirmed the diagnosis of EBV-MCUs and the last serologic evaluation finally showed increasing EBV-DNA-emia. Unfortunately, before admission to the Surgery Room, the patient became septic, most likely from bacterial superinfection. After a cardiac arrest, he finally died. Conclusion: Massive intestinal bleeding is a rare major complication after HSCT. It is important to properly recognize the etiology among massive chemotherapy-induced mucositis, acute Graft versus Host Disease (aGvHD), and bacterial, fungal, or viral infections. Not only CMV-related infections but also EBV-related lesions should be considered, especially in patients previously treated with intense immunosuppressive therapies. Even if EBV-MCU is known to have an indolent course here we described an aggressive course, maybe related to intense immunosuppression and inflammatory background. These cases may need additional treatments other than conservative management. Besides, strict observation should be done to recognize evolution towards systemic disease (PTLDs) and the need for more intensive treatment with chemotherapy.